2011
DOI: 10.1186/1471-2342-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Does the principle of minimum work apply at the carotid bifurcation: a retrospective cohort study

Abstract: BackgroundThere is recent interest in the role of carotid bifurcation anatomy, geometry and hemodynamic factors in the pathogenesis of carotid artery atherosclerosis. Certain anatomical and geometric configurations at the carotid bifurcation have been linked to disturbed flow. It has been proposed that vascular dimensions are selected to minimize energy required to maintain blood flow, and that this occurs when an exponent of 3 relates the radii of parent and daughter arteries. We evaluate whether the dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…9 This software requires identifications of points within the ICA, external carotid artery (ECA), and common carotid artery (CCA). The user-defined points were automatically connected using a path of lowest cost to form a "sketch" of the artery tree.…”
Section: Reconstruction Of 3-dimensional Carotid Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…9 This software requires identifications of points within the ICA, external carotid artery (ECA), and common carotid artery (CCA). The user-defined points were automatically connected using a path of lowest cost to form a "sketch" of the artery tree.…”
Section: Reconstruction Of 3-dimensional Carotid Arterymentioning
confidence: 99%
“…9 The measures of carotid artery geometry were defined according to methods described previously. 8 The bifurcation angle was the angle between the ICA and ECA.…”
Section: Measurement Of Carotid Artery Geometrymentioning
confidence: 99%
“…Others have shown that the exponent might be between 2.42 and 3 when the non--Newtonian behaviour of the blood is accounted for (Revellin et al, 2009). Besides these theoretical studies, experimental measurements have reported values ranging between 2 and 3 on diverse cardiovascular territories, and using diverse methodologies (Beare et al, 2011;Finet et al, 2008;Ingebrigtsen et al, 2004;Mittal et al, 2005;Rossitti and Lofgren, 1993b;van der Giessen et al, 2011). With rare exceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the principle of minimum work the AR would range between 1.10 for turbulent flow in larger arteries and 1.26 for laminar flow in smaller arteries (Uylings, ). From literature we know that in the human vasculature the range of AR is much larger than this theoretical range (Hutchins et al, ; Hardy‐Stashin et al, ; Fanucci et al, ; Papageorgiou et al, ; Aharinejad et al, ; Beare et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…In the past, data of branching patterns of an arterial tree were gathered using manual measurements on ex vivo and in vivo specimens (Koike et al, ; Horsfield and Woldenberg, ; Papageorgiou et al, ; MacLean et al, ; Wang et al, ; Rossitti and Löfgren, ; Zamir, ; Mittal et al, ; Cassot et al, ). More modern techniques utilize newer three dimensional (3D) imaging techniques such as computed tomography angiography (CTA) and magnetic resonance imaging (MRI) for in vivo capturing of larger arteries and micro‐computed tomography (micro‐CT) and confocal laser microscopy for capturing highly detailed in vivo and ex vivo vascular networks (Cassot et al, ; Nordsletten et al, ; Beare et al, ).…”
mentioning
confidence: 99%